Effect of TiO2/Al2O3 hybrid nanofluid and irradiation time on solar photovoltaic thermal performance - Arina Manasikhana, Dita; Permanasari, Avita Ayu; Puspitasari, Poppy; Mohd Rosli, Mohd Afzanizam; Sukarni, Sukarni; Kusumaningsih, Haslinda; Dzulfikar, Muhammad (2023)
Photovoltaic thermal (PVT) is a technology capable of converting solar energy into energy in the form of electricity and thermal (heat). Absorption of solar thermal energy can cause PVT to experience a high temperature increase which affects the efficiency of electricity that can be generated by PVT. Nanofluid is a fluid with high thermal conductivity that can be used as a coolant to absorb the high temperature generated by PVT and recover some of the energy lost as heat to increase the efficiency of PVT. The combination of two nanoparticles as a hybrid nanofluid was produced by mixing 1000 ml distilled water with TiO2/Al2O3 hybrid nanoparticles (80:20) of 0.1% with irradiation time for 60 minutes using light intensity of 1200 W/m2. The results showed that TiO2 nanofluid had the best thermal and electrical efficiency compared to hybrid nanofluid, Al2O3 nanofluid, and distilled water. Thermal efficiency decreased due to the long irradiation time with constant intensity causing ineffective cooling over time, while electrical efficiency increased due to heat reduction on the PVT surface, but after 15 minutes there was a decrease in electrical efficiency caused by the PVT surface overheating.